IMPROVING BASIC TEACHING SKILLS OF PRE-SERVICE TEACHER OF ISLAMIC RELIGIOUS EDUCATION TEACHERS WITH PROJECT BASED LEARNING STRATEGIES IN THE PANDEMIC PERIOD - Sukmawati, Fatma (Journal of Islam and Science, 2021)
The basic teaching skills of pre-service of teacher Islamic religious education who have not been optimal have caused a decrease in the quality of the actual implementation of field teaching practices. The purpose of this study was to improve the teaching skills of Pre-service teacher of Islamic religious education teachers using the Project Based Learning strategy during the Pandemic. This type of research uses Classroom Action Research (CAR). The research subjects were 65 people. Data collection techniques using observation. The results showed that through the use of project based learning strategies to improve basic teaching skills with an average value of 72 in cycle 1 and an average value of 83.4 in cycle 2. For future research, it is recommended that the application of teaching practice practice should apply all basic teaching skills with some practice times with sufficient time estimation, as well as assessments carried out by learning experts.